Experimental cultivation of the red seaweed, Gracilaria gracilis (Rhodophyta) in land-based tank culture systems on abalone farms in the Western Cape, South Africa - Njobeni, Asanda (Department of Biological Sciences, 2014)
Includes bibliographical references (leaves 91-111).